Effects of ginger-loaded chitosan nanoparticles on growth, morphological and biochemical attributes of Sesamum indicum L. - Hunaira Nasreen; Abdul Ghaffar; Sumaira Yousaf (PLoS ONE, 2026)
Chitosan nanoparticles (ChNPs) have gained attention due to their biodegradability, biocompatibility, and non-toxicity, and are found in a wide range of agricultural products. The green synthesis and characterization of ChNPs using ginger extract were evaluated for their effects on biochemical and morphological parameters in sesame ( Sesamum indicum L.). Ginger-loaded ChNPs synthesis, size, structure, morphology, and crystallinity were confirmed via UV-Vis spectrophotometry, DLS (151.7 nm, ± 30 mV), FTIR, SEM, and XRD, respectively. Foliar applications of ChNPs (50 mg L -1 and 100 mg L -1 ) and pesticides confidor (2.5 mL L -1 ) confidor + talstar (2.5 mL L -1 ) were applied at flowering and capsule stages under controlled conditions. ChNPs at 100 mg L ⁻ ¹ significantly enhanced plant height 5.3%, leaf area 26.5%, number of capsules 43.6%, capsule weight (12.4%), stem diameter 34.4%, total chlorophyll 11.9%, and catalase activity 53.1% compared with the control (P < 0.05), while reducing peroxidase 85.7% and PAL 59%. In contrast, confidor and confidor + talstar treatments showed compromised effects. Present research demonstrated that green synthesized ChNPs have good potential for use in agriculture and can significantly increase sesame growth and yield.